Musical Groups in the Movies, 1929-1970. (McFarland and Company Inc, 2009)
Hundreds of musical groups have appeared in at least one film from 1929 through 1970. This is a reference book devoted to these groups. Most entries include a brief description of the musical group, a list of the main singers or performers and, when av.